Infectious Diseases of Poverty reviewer acknowledgement 2015 - Zhou, Xiao-Nong (Infect Dis Poverty, 2016)
The editors of Infectious Diseases of Poverty would like to thank all our reviewers who have contributed to the journal in volume 4 (2015).